Effectiveness of Bacillus-Based Biofertilizer on Growth and Biomass of Corn in Low-Phosphorus Soil under Pot Experiment - Reginawanti Hindersah; Betty Natalie Fitriatin; Aliya Zahrah Adawiah; Testarosa Testarosa; Yeni Wispa Dewi (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2026)
Biofertilizers provide plants with essential nutrients through nitrogen fixation and phosphate solubilization. A pot experiment was conducted to examine the effects of different types of biofertilizers on plant growth, biomass, and rhizosphere microbial populations in corn grown in soil with low available phosphorus. The greenhouse experiment was designed using a completely randomized block design to test three biofertilizer types and two control treatments. The tested biofertilizers included a solid inoculant of phosphate-solubilizing bacteria, a liquid inoculant of a mixture of nitrogen-fixing bacteria and phosphate-solubilizing bacteria, and a Bacillus-based liquid biofertilizer. The results showed that soil inoculation with biofertilizer in soil enriched with organic matter did not alter leaf number or shoot height in 4-week-old corn; however, it increased both parameters compared to corn grown in soil without cow manure. Despite reduced root growth after biofertilizer inoculation, the corn dry weight was significantly higher following Bacillus-based biofertilizer application than with other biofertilizers. The experiment found that Bacillus was more effective for increasing corn biomass during vegetative growth in soil enriched with organic matter. The results indicate that the effectiveness of heterotrophic biofertilizer microbes is determined by soil organic matter.